THE INFLUENCE OF GOOD GOVERNANCE, COMMUNITY PERCEPTION AND GOVERNMENT INTERNAL CONTROL SYSTEMS ON THE QUALITY OF PUBLIC SERVICES: Study at Cidamar Village Office, Cianjur Regency - Yono, Yono; Hamdani, Deni (Journal of Accounting Inaba, 2022)
The purpose of this study was to determine the effect of good governance, public perception and internal control system on the quality of public services. The data was collected through interviews, field research and library techniques as well as distributing questionnaires to 96 respondents. Sampling using non-probability sampling with purposive sampling. To measure the influence of the sample used classical assumption test analysis, multiple linear regression analysis and the coefficient of determination and hypothesis testing. Data processing using the application of Statistical Product and Service Solution version 25. The results showed that hypothesis testing (t test) obtained the results: (1) Good governance affects the quality of public services where count is -2.096 smaller than table -1.293 with a significance level of perception of 0.04 <0.05 (2) Public affects the quality of public services where count is 8.037 greater than table 1.293 and a significance value of 0.00 <0.05 (3) Government Internal Control System affects the quality of public services where count is 1.361 greater than table 1.293 and a significance level of 0.108>0.05. The results of hypothesis testing (f test) of good governance, public perception, and internal control systems affect the quality of public services where count is 25.829 which is greater than table 2.70 with a significance level of 0.000 <0.05.